Investigation of the reaction of dithiocarbamic acid salts with trimethyl orthoformate and styrene epoxide. Issue 51 (23rd December 2015) - Ziyaei Halimehjani, Azim; Hajilou Shayegan, Mojtaba; Poshteh, Shiva Shakori; Amani, Vahid; Notash, Behrouz; Hashemi, Mohammad M.
Graphical abstract: Abstract: The reaction of dithiocarbamic acid salts with trimethyl orthoformate in the presence of BF3 ·OEt2 was investigated to give 4-( N, N -dialkyldithiocarbamato)-2-dialkyliminio-1, 3-dithietane tetrafluoroborates in good yields. Additionally, a one-pot procedure for the synthesis of 2-iminium-1, 3-dithiolanes from the BF3 ·OEt2 catalyzed reaction of dithiocarbamic acid salts with styrene epoxide is described.